The Relationship between Leadership Style and Corporate Financial Compensation to Employee Job Satisfaction - Hadiansyah Ma'sum; Syamsul Hadi Senen (Fundamental and Applied Management Journal, 2023)
The study aims to determine the effect of leadership style and financial compensation on job satisfaction of employees of PT Astra International TBK Toyota Sales Operation (Auto2000) Pasteur Bandung. The population in this study were all employees within the scope of PT Astra international TBK Toyota Sales Operation (Auto2000) Pasteur Bandung as many as 80 people. Data collection is done by using observation, documentation, interview, and questionnaire methods. The data analysis technique used is multiple regression analysis and Multiple Correlation Coefficient Analysis and Coefficient of Determination Analysis using the IBM Statistical for Product and Service Solution (SPSS) version 21 program. The results of this study indicate that the two independent variables, namely Leadership Style (X1) and Financial Compensation (X2) have a relationship or influence individually or partially and a relationship together or simultaneously on the dependent variable, namely Job Satisfaction. The correlation coefficient of 0.978 is in the interval 0.91-0.99 which indicates the strength of the relationship between the independent variable and the dependent variable is very strongly correlated. The coefficient of determination of 0.965 shows that the independent variable to predict the dependent variable is 96.5%, the remaining 4.4% is influenced by other factors.